A Case of Paediatric Anti-Glomerular Basement Membrane Disease Associated with Thrombotic Thrombocytopenic Purpura - Joseph McAllister; Pradeep Nagisetty; Kay Tyerman (Case Reports in Nephrology)
Anti-GBM disease is a rare vasculitis that causes rapid progressive glomerulonephritis and pulmonary haemorrhage. It is usually an adult diagnosis with isolated paediatric cases reported. Thrombotic thrombocytopenic purpura (TTP) is a rare thrombotic microangiopathy mainly affecting adults that causes multiorgan ischaemia, microangiopathic haemolytic anaemia, and thrombocytopenia. We present the first paediatric case of concurrent anti-GBM disease and TTP. A 14-year-old boy presented with acute kidney failure and severe pulmonary haemorrhage due to anti-GBM disease, confirmed on auto-antibody testing. There was thrombocytopenia and moderately low ADAMTS13 activity suggestive of TTP. The renal prognosis was poor with a need for dialysis. He was severely unwell with pulmonary haemorrhages requiring the use of extracorporeal membrane oxygenation (ECMO). His disease was treated with corticosteroids, plasma exchange (PEX), rituximab, and cyclophosphamide, resulting in remission. Anti-GBM disease is rare in children but should be considered in those presenting with acute kidney injury, particularly where there has been exposure to pulmonary irritants. An aggressive presentation warrants aggressive treatment with methylprednisolone, PEX, and cyclophosphamide. Rituximab may benefit patients that have concurrent TTP. TTP may exacerbate pulmonary disease, but complete respiratory recovery is possible. Disease relapse is rare in the paediatric age group, and these patients are candidates for kidney transplantation.